A Comprehensive Analysis of the Effectiveness of AI Platforms in Improving Student Educational Skills - Khudai Qul Khaliqyar; Shairagha Katebzadah; Musawer Hakimi (MultiTech Publisher, 2023)
This study explores the profound impact of Artificial Intelligence (AI) on education in diverse academic settings, aiming to understand how AI integration influences educational outcomes and student experiences across various faculties and universities. With the objective of providing a comprehensive analysis, the research employs a mixed-methods approach involving 200 participants from Medical, Computer Science, Engineering, Economics, and Education faculties. Surveys gauge AI educational skills, platform utilization, and academic performance impact, complemented by qualitative insights from interviews. Quantitative analysis reveals a significant enhancement in AI educational skills positively affecting academic performance, while qualitative findings enrich overall perceptions across faculties. Varied AI platform utilization and their impact on motivation and critical thinking skills emerge as noteworthy outcomes. The study underscores AI's transformative potential in education, with implications for curriculum design and learning strategies. As AI continues to shape education, understanding its multifaceted impact becomes crucial for educators, institutions, and policymakers, providing valuable insights for optimizing AI in diverse academic disciplines.